Implementation of Security in LoRaWAN Network Using Speck Algorithm and Message Authentication Code - Carolin, Arselliana Khoirun Nisa; Ardiansyah, Rizky; Koesmarijanto, Koesmarijanto (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2024)
Long Range (LoRa) is a wireless technology that provides long-range and low-power communication. However, LoRa still has weaknesses when it comes to data transmission processes, making it vulnerable to attacks. One of the common attacks during data transmission in LoRaWAN is sniffing or data theft. This research aims to create a system that can protect LoRa devices from attacks that could lead to data leakage to unauthorized parties. The research findings indicate that implementing encryption systems on LoRa using Speck and Message Authentication Code algorithms can secure LoRa devices from sniffing attacks, preventing sniffers or attacking nodes from successfully reading or altering messages sent by the sender. The implementation of encryption systems on devices affects network performance, such as packet errors, packet loss, delay, and throughput. Based on 100 experiments conducted, the encrypted system resulted in 7 packet errors and 15 packet losses, while the unencrypted devices produced 2 packet errors and 9 packet losses. The average delay for messages generated by unencrypted devices was 83 milliseconds, whereas the average delay for encrypted messages was 1.109 milliseconds or 1 second 109 milliseconds. The throughput for devices with encryption had an average value of 3224.146 KBps, while devices without encryption had an average value of 6286.252 KBps. The LoRa used in the research operates at a frequency of 433 MHz. This system employs Speck 128-bit encryption, allowing a maximum message size of 16 characters. Based on the research findings, devices with encryption affect network performance by increasing the number of packet errors and losses, resulting in longer delays and decreased throughput.